Children's Play and Culture Learning in an Egalitarian Foraging Society. Issue 3 (May 2016) - Boyette, Adam H.
Abstract : Few systematic studies of play in foragers exist despite their significance for understanding the breadth of contexts for human development and the ontogeny of cultural learning. Forager societies lack complex social hierarchies, avenues for prestige or wealth accumulation, and formal educational institutions, and thereby represent a contrast to the contexts of most play research. Analysis of systematic observations of children's play among Aka forest foragers ( n  =   50, ages 4–16, M  =   9.5) and Ngandu subsistence farmers ( n  =   48, ages 4–16, M  =   9.1) collected in 2010 illustrates that while play and work trade off during development in both groups, and consistent patterns in sex‐role development are evident, Aka children engage in significantly less rough‐and‐tumble play and competitive games than children among their socially stratified farming neighbors.